Evaluation of mechanical beaters in coffee harvesting / evaluación de batidores mecánicos en la cosecha del café (2013)
Abstract: Two portable devices were evaluated for coffeeharvesting. The Italian-made MAIBO beater (harvest tool),used for coffee harvesting in Brazil, and the beater designedby Cenicafé (CENICAFE-I), which removes fruits by applyingpressure to the clusters that have a higher content of ripe fruits. The research was conducted in two stages. In the first, the two beaters were compared using 60 experimental units of seven trees each. The CENICAFE-I beater presented the better quality in the harvested coffee and used an equal amount of time per tree. In the second stage, the performance of the CENICAFE-I beater was compared with the traditional manual method, using an commutative experimental design with 50 plots (replicates) of 14 trees each; randomly assigning seven trees in each plot to each method. The CENICAFE-I beater, without a manual resweep, increased the operational yield by 305.7% as compared to that of the traditional manual method. With an immediate, manual resweep, the operational yields were equal for the two methods. The quality of the coffee collected with the CENICAFE-I was lower than that of manual harvesting and was not acceptable by Colombian standards. In order to reduce the cost of harvesting by 10% when using a pneumatically actuated CENICAFE-I beater, one must achieve yields greater than 40 kg h-1 or 60 kg h-1 when operating 400 or 200 h/year, respectively. / Resumen. Se evaluaron dos dispositivos portátiles en la cosecha del café. El batidor MAIBO de fabricación italiana, utilizado en Brasil en la cosecha del café y un batidor diseñado en Cenicafé (CENICAFE-I) para desprender frutos comprimiendolos glomérulos que presenten mayor concentración de frutosmaduros. La investigación se realizó en dos etapas. En laprimera, se compararon los dos batidores utilizando para cada uno 60 unidades experimentales, de siete árboles cada una. Se seleccionó al batidor CENICAFE-I por presentar mejor calidad de café recolectado e igual tiempo empleado por árbol. En la segunda etapa, se comparó el desempeño en cosecha del batidor CENICAFÉ-I con el método manual tradicional, utilizando un diseño experimental conmutativo, con 50 parcelas (repeticiones) de 14 árboles cada una, asignando aleatoriamente siete árboles a cada método en cada parcela. Con el batidor CENICAFÉ-I sin repase manual se incrementó el rendimiento operativo en un 305,7% con relación al observado con el método manual tradicional. Con repase manual inmediato los rendimientos operativos fueron iguales con ambos dispositivos. La calidad del café recolectado con el batidor CENICAFE-I fue inferior ala obtenida con la cosecha manual y no es aceptable para losestándares colombianos. Para disminuir un 10% el costo de larecolección de café, utilizando el equipo CENICAFE-I accionadoneumáticamente, se requiere alcanzar rendimientos superiores a 40 kg h-1 y 60 kg h-1, con tiempos de trabajo de 400 y 200 h/ año, respectivamente.